Evaluation Of Social Assistance Programs In Reduction Poverty During The Covid-19 Pandemic: Economic Perspective - Nasution, Armin Rahmansyah; Aini, Lathifah; Manik, Citra Wulandari; Runi , Naila Ananda (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Socioeconomic conditions in many countries, including Indonesia, have been significantly impacted by the COVID-19 epidemic. To alleviate poverty during the pandemic, the government has launched several social assistance programs, including Direct Cash Assistance (BLT). This research aims to determine and explain the impact of social assistance programs in reducing poverty during the COVID-19 pandemic in Medan City. The analytical method used is qualitative and uses the literature review method. The data collection method used in this research is called secondary data collection. The research uses content analysis techniques, where this method are used to analyze data, news sites, theses, and official government documents related to social assistance programs during the COVID-19 epidemic. The results of the research show that social assistance had a positive effect during the pandemic where the number of poor people in Medan City in 2020 was 183.54 thousand people, this figure only decreased slightly compared to one year before the pandemic occurred (2019) when the number of poor people was 183.79 thousand souls. However, social assistance alone is not sufficient and efficient to reduce poverty levels significantly. For social assistance to have a significant impact, it must be provided quickly, precisely, and on time.